Pediatric dilated cardiomyopathy: a review of current clinical approaches and pathogenesis - Malinow, Ian; Fong, Daniel C.; Miyamoto, Matthew; Badran, Sarah; Hong, Charles C. (Frontiers in Pediatrics, 2024)
Pediatric dilated cardiomyopathy (DCM) is a rare, yet life-threatening cardiovascular condition characterized by systolic dysfunction with biventricular dilatation and reduced myocardial contractility. Therapeutic options are limited with nearly 40% of children undergoing heart transplant or death within 2 years of diagnosis. Pediatric patients are currently diagnosed based on correlating the clinical picture with echocardiographic findings. Patient age, etiology of disease, and parameters of cardiac function significantly impact prognosis. Treatments for pediatric DCM aim to ameliorate symptoms, reduce progression of disease, and prevent life-threatening arrhythmias. Many therapeutic agents with known efficacy in adults lack the same evidence in children. Unlike adult DCM, the pathogenesis of pediatric DCM is not well understood as approximately two thirds of cases are classified as idiopathic disease. Children experience unique gene expression changes and molecular pathway activation in response to DCM. Studies have pointed to a significant genetic component in pediatric DCM, with variants in genes related to sarcomere and cytoskeleton structure implicated. In this regard, pediatric DCM can be considered pediatric manifestations of inherited cardiomyopathy syndromes. Yet exciting recent studies in infantile DCM suggest that this subset has a distinct etiology involving defective postnatal cardiac maturation, such as the failure of programmed centrosome breakdown in cardiomyocytes. Improved knowledge of pathogenesis is central to developing child-specific treatment approaches. This review aims to discuss the established biological pathogenesis of pediatric DCM, current clinical guidelines, and promising therapeutic avenues, highlighting differences from adult disease. The overarching goal is to unravel the complexities surrounding this condition to facilitate the advancement of novel therapeutic